Kenya [in Strategies and priorities for African agriculture] - Thurlow, James; Kiringai, Jane; Gautam, Madhur (International Food Policy Research Institute, 2012)
Kenya’s economy is diverse, with both agricultural and industrial potential. However, the economy has not performed especially well over the past two decades, and evidence suggests that poverty and inequality has not declined much. Therefore, it is imperative that Kenya’s government foster stronger growth and a process of income generation that benefits the broader population. As discussed in the next section, numerous studies emphasize the importance of rural development in Kenya, largely because a majority of the population, especially poor households, lives in rural areas, where they rely heavily on agricultural incomes. Urban households also depend on rural areas as a source of food and as a market for nonagricultural goods. However, Kenya’s ninth National Development Strategy has not taken a particularly optimistic view of agriculture’s potential contribution to economic growth—it targets an annual growth rate of around 4 percent per year, with agriculture growing at a little more than 3 percent (Kenya 2002).